2021
DOI: 10.31234/osf.io/x2cqw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing Causal Explanations of Viewing Time Measures of Sexual Interests

Abstract: The term viewing time (VT) effect refers to a phenomenon whereby respondents typically take longer to judge the sexual attractiveness of targets from sexually preferred (versus nonpreferred) categories. Although frequently characterized as an unobtrusive measure of respondents’ sexually motivated reactions to the stimulus images themselves, the typical pattern of response times might be sufficiently explained by the task demands of the seemingly less relevant rating task. Utilizing three different VT variants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In other words, we cannot directly discern whether some fathers gazed longer at child images because of their sexual interest in children or, rather, because those images were particularly surprising or disturbing. Since this interpretation is in contrast with the empirically supported cold cognitive processes explanation of VT effects (e.g., Schmidt et al, 2021), future VT studies involving fathers could help clarifying whether this explanation holds in fathers specifically.…”
Section: The Utility Of Viewing Time Measures To Discriminate Partici...mentioning
confidence: 77%
See 2 more Smart Citations
“…In other words, we cannot directly discern whether some fathers gazed longer at child images because of their sexual interest in children or, rather, because those images were particularly surprising or disturbing. Since this interpretation is in contrast with the empirically supported cold cognitive processes explanation of VT effects (e.g., Schmidt et al, 2021), future VT studies involving fathers could help clarifying whether this explanation holds in fathers specifically.…”
Section: The Utility Of Viewing Time Measures To Discriminate Partici...mentioning
confidence: 77%
“…In contrast, deliberative mate selection processes (i.e., cold cognitive processes) describes the delay as being explained by the length of time it takes to appraise the sexual attractiveness of the stimuli (i.e., feature-checking), with longer delay for attractive stimuli, as there are more features (e.g., gender, physical appearance) to be assessed than unattractive stimuli. Using variants of VTs, Schmidt et al (2021) found that VT effects could be explained by the cold cognitive process hypothesis that more information is required to process sexually preferred than non-preferred targets, resulting in longer VTs (see also Imhoff et al, 2012;Pohl et al, 2016).…”
Section: Viewing Time Measures Of Sexual Interest In Childrenmentioning
confidence: 99%
See 1 more Smart Citation